“I moved from simply being to actively living.” A qualitative study on peer mentorship camps for adults with acquired brain injury - Pia Wedege; Silje Mæland; Anestis Divanoglou; Charlotta Hamre; Frank Eirik Abrahamsen (International Journal of Qualitative Studies on Health & Well-Being)
Purpose This study explored the experiences of an Active Rehabilitation peer mentorship camp on individuals with acquired brain injury (mentees) and its impact on their daily lives. Methods The research involved field observations and longitudinal interviews with 18 mentees attending an Active Rehabilitation camp in Norway. Data were narratively analyzed using the Self-determination theory for insight and discussion. Results Three themes were constructed from the analysis. The first theme, “Striking a balance between rest and activity,” reflects how mentees managed post-injury fatigue and how camp experiences enhanced their understanding and coping strategies. The second theme, “Rebuilding who I am,” addresses stigma, reduced self-esteem, and acceptance challenges faced by mentees, revealing positive effects from camp participation. The third theme, “Finding a new flock,” describes the reduction in social circles after injury and how interactions at the camp expanded their peer networks during and after the camp. Conclusions Active Rehabilitation camps enhance community-based rehabilitation for individuals with acquired brain injury by improving knowledge, boosting self-esteem, and broadening social networks. It is recommended that camp providers assess the impact of room-sharing and devise strategies for personalizing camp activities and effectively matching mentees and peer mentors.